Myocardial Bridge and Acute Plaque Rupture - Leor Perl MD; David Daniels MD; Jonathan Schwartz MD; Shige Tanaka MD, PhD; Alan Yeung MD; Jennifer A. Tremmel MD; Ingela Schnittger MD (SAGE Publishing, 2016)
A myocardial bridge (MB) is a common anatomic variant, most frequently located in the left anterior descending coronary artery, where a portion of the coronary artery is covered by myocardium. Importantly, MBs are known to result in a proximal atherosclerotic lesion. It has recently been postulated that these lesions predispose patients to acute coronary events, even in cases of otherwise low-risk patients. One such mechanism may involve acute plaque rupture. In this article, we report 2 cases of patients with MBs who presented with acute coronary syndromes despite having low cardiovascular risk. Their presentation was life-risking and both were treated urgently and studied with coronary angiographies and intravascular ultrasound. This latter modality confirmed a rupture of an atherosclerotic plaque proximal to the MB as a likely cause of the acute events. These cases, of unexplained acute coronary syndrome in low-risk patients, raise the question of alternative processes leading to the event and the role MB play as an underlying cause of ruptured plaques. In some cases, an active investigation for this entity may be warranted, due to the prognostic implications of the different therapeutic modalities, should an MB be discovered.